Sustainability Index of Community-Based Tourism in Malang Regency - Puspitosari, Wida Ayu; Susanti, Anik; Arawindha, Ucca (International Journal of Social and Local Economic Governance, 2022)
Tourism potential in Malang Regency has not been managed optimally. To address this problem, the local authority applies the concept of tourism village that considers the sustainability of socio-economic and ecological aspects. Therefore, the concept of community-based tourism (CBT) needs to be exercised in the development of rural tourism. The purpose of this study is to assses and analyze sustainability Index of community-based tourism in Pujon Kidul. There are five indicators on economic, social, ecological, infrastructure and institutional aspects to discuss. The research method applied in this study is mix method that combines qualitative and quantitative. The result shows that sustainability index of community-based tourism in Pujon Kidul is relatively high with the attractions of cafÃ© Sawah. Sustainability can be perceived from the good infrastructure and economic impact and how it affected the community